The The effects of bio-fertilization and two levels of chemical fertilization on wheat (Triticum aestivum L.) under drought conditions - saad, Dina A.; Al-Shahwany, Ayyad W.; Aboud, Hadi M. (Iraqi Journal of Science, 2021)
A filed experiment was conducted to consider the impacts of bio-fertilizers (Azotobacter chroococcum and Glomus mosseae) and two levels of chemical fertilization ( 50% and 100% of recommended dose) on proline content and activities of antioxidant enzymes (catalase and peroxidase) in wheat Triticum aestivum L. cultivar IPA 99 under drought conditions (50% and 20% of soil field capacity). Bio-fertilization involved treatment with A. chroococcum (Azoto) and G. mosseae (AMF), singly or in combination. The experiment was conducted by applying a Randomized Complete Block Design (RCBD) with three replications. The results of this study showed that the treatment utilizing Azoto+AMF fertilizer with concentrated chemical fertilizer (100%) significantly decreased proline content and the activities of antioxidant enzymes under drought conditions. In addition, the percentage of mycorrihzal root infection was increased. The lowest values of proline content and catalase and peroxidase activities (3.35 µmole/g, 84.52 unit/ml, 90.90 unit/ml, respectively) were achieved by the application of combined bio-fertilizers with 100% of chemical fertilizer and 50% water deficit. The combined bio-fertilizer application with 50% of chemical fertilizer and 20% water deficit achieved the maximum mycorrihzal infection percentage (90%).